Peranan Media Sosial dalam Gerakan Dakwah dan Politik Islam di Indonesia - Jelita Hasibuan; Hasan Sazali (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This paper examines the role and potential of social media in the propagation of Islamic politics in Indonesia. This study aims to describe the role and potential of social media in Islamic political da'wah in Indonesia. The method used in obtaining data is a qualitative method which is carried out by taking data references from books, journals, and trusted news pages related to the theme of social media relations and da'wah. The results of the study show that social media and da'wah have a very close relationship. From social media, da'wah can be shared and distributed to be known by the public. Social media is used to preach to invite to the right path and keep away from what is evil, to achieve the pleasure of Allah SWT. With social media, da'wah can also capture all audiences and have a large mass and can expand the reach of preaching, especially with the presence of the YouTube application.